The Effect of Fried Bean Consumption on Milk Production in Postpartum Primigravida Mothers at the Lakessi Health Center, Parepare City in 2024 - Arifa Usman; Arini Purnamasari; Rismawati; Rosdiana; Andi Misnawati (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: Fried beans are very high in protein and unsaturated fats. Protein is very good to help the mother's birth scar heal quickly. Then the fat content between postpartum mothers who consume fried beans and those who do not consume fried beans to milk production will also help how to make milk come out a lot after giving birth so that mothers do not need to use supplements or lactation massage Methods: This study used a quantitative type of research. The design used in this study is a quasy experiment design using the pre test and post test nonequivalent control group approach. Results: This study showed that the feeding of fried beans on the breast milk production of postpartum mothers had. Conclusion: This study concluded that there is an effect of feeding fried beans on the breast milk production of primigravida postpartum mothers in the working area of the Lakes Health Center in Parepare City in 2024.